Perspectives in criminology / edited by S. Venugopal Rao - Rao, S.Venugopal (ed.) (New Delhi, 1988)
This paper discusses the recent emergence of "Criminal Justice" as a multidisciplinary field of study which draws much of its intellectual sustenance from such established disciplines as sociology-criminology, economics, political science, and history.
Keywords: Criminology